Narrowing the Tax Gap Through Presumptive Taxation - Logue, Kyle D.; Vettori, Gustavo G. (Columbia Journal of Tax Law, 2011)
This Article highlights the primary tax enforcement problem in the United States, that of noncompliant small and medium-sized businesses (“SMBs”), and it explores the possibility of a radical solution: shifting away from the current system, which attempts to tax the actual income of each business, and toward a system that taxes only a rough approximation (or probabilistic estimate) of business income. This sort of presumptive tax approach has been used for years in developing economies, where the problem of SMB noncompliance is even worse than in the U.S. This Article argues that the time has come to at least consider various ways of taxing SMBs in the U.S. on a presumptive basis as well. The particular regime that the Article spends the most time developing is a type of modified gross receipts (MGR) tax of the sort that is used in some developing economies. Under our version of the MGR approach, SMB taxpayers would be taxed on a rough estimate of their annual income using (a) their reported gross receipts and (b) presumed profit ratios based on historical line-of-business profit margins. Whether such a regime would make sense depends on a number of key unanswered questions, including how narrowly and accurately such historical line-of-business profit percentages can be drawn and at what cost. We also discuss whether such a regime should be mandatory or optional; and, if mandatory, whether it should be only a mandatory minimum (like the alternative minimum tax) or both a minimum and maximum. Moving to an MGR approach to taxing SMB income would require a major change in the Internal Revenue Code. As a more modest alternative, the Article also considers instead having the IRS begin to use presumptive-tax principles as part of their audit strategies. If the Service could credibly commit to applying some form of presumptive/probabilistic tax system in its auditing decisions (perhaps as part of the Discriminate Index Function), and if taxpayers reacted rationally to such an audit policy, the results could be similar to an optional presumptive business income tax.